2021
DOI: 10.1007/s40610-021-00145-4
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Senescence in Idiopathic Pulmonary Fibrosis

Abstract: Cellular senescence (CS) is increasingly implicated in the etiology of age-related diseases. While CS can facilitate physiological processes such as tissue repair and wound healing, senescent cells also contribute to pathophysiological processes involving macromolecular damage and metabolic dysregulation that characterize multiple morbid and prevalent diseases, including Alzheimer’s disease, osteoarthritis, atherosclerotic vascular disease, diabetes mellitus, and idiopathic pulmonary fibrosis (IPF). Preclinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 115 publications
0
26
0
2
Order By: Relevance
“…On the one hand, senescence may act as a mechanism limiting fibrosis in liver, heart, and wound healing (Jun & Lau, 2010 ; Krizhanovsky et al, 2008 ; Meyer et al, 2016 ). On the other hand, it has also been proposed that senescence can promote fibrosis in other settings, including lung, kidney, and pancreas fibrotic diseases (Kellogg et al, 2021 ; Schafer et al, 2017 ). Our results clearly show the downregulation of myofibroblast markers in cellular models of senescence.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, senescence may act as a mechanism limiting fibrosis in liver, heart, and wound healing (Jun & Lau, 2010 ; Krizhanovsky et al, 2008 ; Meyer et al, 2016 ). On the other hand, it has also been proposed that senescence can promote fibrosis in other settings, including lung, kidney, and pancreas fibrotic diseases (Kellogg et al, 2021 ; Schafer et al, 2017 ). Our results clearly show the downregulation of myofibroblast markers in cellular models of senescence.…”
Section: Discussionmentioning
confidence: 99%
“…Aging is an important factor in IPF and can give rise to non-functional and pro-inflammatory senescent cells [ 35 ]. Senescence has gained significant interest in the past decade, and strategies to clear senescent cells during IPF are actively tested [ 36 , 37 , 38 , 39 ]. Beyond senescence, hypoxia is a major hallmark of IPF, where scar tissue deposition hampers gas exchange.…”
Section: The Physiopathology Of Pulmonary Fibrosismentioning
confidence: 99%
“…Additionally, some studies have highlighted that a variety of aging-related pathways are activated in epithelial cells, fibroblasts, and progenitor cells in the lungs of patients with IPF (Mora et al, 2017;Chen et al, 2019); these activated pathways promote abnormal secretory phenotype in lung epithelial cells, augment the resistance of myofibroblasts to apoptosis, and accelerate IPF progression. In the lung biopsies of patients with IPF, the level of SA-β-gal, a specific cellular senescence marker, was increased compared to that in patients with chronic obstructive pulmonary disease or hypersensitivity pneumonitis (Kellogg et al, 2021). Kim et al (2021) evaluated the genomic profile of fibrotic and normal lung tissues and found that the core molecular network of IPF featured p53 signaling pathway and cellular senescence.…”
Section: Introductionmentioning
confidence: 99%